2017
DOI: 10.3892/ol.2017.5890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of high-sensitivity C-reactive protein tests for the diagnosis of hepatocellular carcinoma in patients with hepatitis B-associated liver cirrhosis

Abstract: Abstract. Hepatocellular carcinoma (HCC) is a common malignant tumor worldwide, with high morbidity and mortality. Chronic infection with hepatitis B virus (HBV) is a major risk factor for the development of hepatocellular carcinoma and the majority (~80%) of hepatocellular carcinoma patients in China exhibit co-morbidity with HBV-associated liver cirrhosis. The goal of reliable early diagnostic and prognostic techniques for HBV-associated HCC remains unrealized. The aim of the present study was to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Furthermore, N. Sativa reduction of hs-CRP reduction comes in agreement with, Alizadeh et al, 2016 who found that N. Sativa reduced hs-CRP in women with rheumatoid arthritis [46]. Along with reduction of IL-6 our results confirm anti-inflammatory effect for N. Sativa in HCC as well as the potential role for hs-CRP as an early diagnostic tool for HCC [47].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, N. Sativa reduction of hs-CRP reduction comes in agreement with, Alizadeh et al, 2016 who found that N. Sativa reduced hs-CRP in women with rheumatoid arthritis [46]. Along with reduction of IL-6 our results confirm anti-inflammatory effect for N. Sativa in HCC as well as the potential role for hs-CRP as an early diagnostic tool for HCC [47].…”
Section: Discussionsupporting
confidence: 89%
“…Ma et al (126) used a high-sensitivity CRP (hs-CRP) assay, which could be quantified as low as 0.04 mg/L of CRP and found that serum hs-CRP levels were significantly elevated in the HCC group compared with those in the non-HCC group and did not correlate with tumor Edmondson grade, TNM stage, or AFP status. Serum hs-CRP had a better performance than AFP (AUROC 0.903 vs. 0.824, sensitivity 84.2 vs. 74.4%, specificity 61.6 vs. 55.6%) for diagnosing HCC, and the diagnostic performance improved when the two indicators were combined (AUROC = 0.998, sensitivity = 94.1%), with similar positive rates between APHC and ANHC patients (86.9 vs. 84.6%) (126), indicating that serum hs-CRP level may be a useful diagnostic biomarker complementary to AFP for ANHC diagnosis. Another study also found that serum CRP-positive rate was significantly higher in the HCC than in the LC (64.15 vs. 37.97%) (127), and serum CRP levels were similar between ANHC and APHC patients.…”
Section: Crpmentioning
confidence: 99%
“…C-reactive protein (CRP) is a non-specific acute-phase protein produced by the liver in response to acute and chronic inflammation, and elevated CRP expression has been detected in multiple tumors and is associated with poor prognosis ( 122 – 125 ). Ma et al ( 126 ) used a high-sensitivity CRP (hs-CRP) assay, which could be quantified as low as 0.04 mg/L of CRP and found that serum hs-CRP levels were significantly elevated in the HCC group compared with those in the non-HCC group and did not correlate with tumor Edmondson grade, TNM stage, or AFP status. Serum hs-CRP had a better performance than AFP (AUROC 0.903 vs. 0.824, sensitivity 84.2 vs. 74.4%, specificity 61.6 vs. 55.6%) for diagnosing HCC, and the diagnostic performance improved when the two indicators were combined (AUROC = 0.998, sensitivity = 94.1%), with similar positive rates between APHC and ANHC patients (86.9 vs. 84.6%) ( 126 ), indicating that serum hs-CRP level may be a useful diagnostic biomarker complementary to AFP for ANHC diagnosis.…”
Section: Blood Biomarkers For Anhc Diagnosismentioning
confidence: 99%
“…The Glasgow score, consisting only of the 2 parameters, CRP and albumin, has been found to be an important and independent prognosticator for several cancer types, including HCC [9-18]. Furthermore, there is evidence that CRP is produced not just by hepatocytes, but also by HCC cells [19]. However, the function, biological role and significance in determining HCC prognosis are still unclear.…”
Section: Abbreviationsmentioning
confidence: 99%